THE INFLUENCE OF BRAND AWARENESS AND BRAND IMAGE ON PURCHASE INTENTION IN ISLAMIC BANKS - Rosa, Aprika; Busyro, Wahyi; Jamillah, Putri; Septianingsih, Rika (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study investigates the influence of Brand Awareness and Brand Image on Purchase Intention in Islamic Banks. The research is motivated by the need for Islamic financial institutions to strengthen their brand positioning as a strategy to attract potential customers in today’s competitive banking industry.The study employed a quantitative approach with multiple linear regression analysis using SPSS software. A total of 100 respondents were selected through probability sampling with a simple random sampling method. Data were collected through a Likert-scale questionnaire consisting of items measuring Brand Awareness, Brand Image, and Purchase Intention.The findings reveal that Brand Awareness has a positive and significant effect on Purchase Intention, while Brand Image also exerts a positive and significant effect on Purchase Intention. These results suggest that customers who are more aware of and hold a positive perception of a brand are more likely to choose Islamic banking products. Strengthening brand awareness and brand image can therefore serve as a competitive advantage, enabling Islamic Banks to increase customer interest, maintain growth, and ensure long-term sustainability in the financial sector.